Marketing Website Of E-Comerce as Production Unit’s Container For All Smk In Surakarta - Setyadi Fajar; Dwi Maryono; Basori Basori (Journal of Informatics and Vocational Education, 2021)
This research is aimed to produce a marketing website for SMK's products to manage the production units in SMK within Solo area and introduce SMK's products to public. His research also aimed to determine the properness of this website. This research uses Research and Development (R & D) research method by Sugiyono. This research includes 5 steps, they are potential and problem analysis, data collection, product design, product validation and product revision. The results of this study show that the website is very proper to use. Score for assessment of the experts system is 89.3% and it is categorized very proper. Assessment of both substance experts is 88.4% and it is categorized as very proper. This website has superiorities that are: 1) integrating the existing SMK production unit in Surakarta, 2) there is a messaging feature. For the weaknesses of this website are: 1) the design is less attractive, 2) the absence of transaction features.